Effect of GnRH on Ovarian Activity in Postpartum Anestrus Sahiwal Cows - Paikra, Dilip; Tiwari, R. P.; Chaturvedani, A. K.; Chandrakar, Choodamani (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A total of 14 Sahiwal cows were selected from bull mother experimental farm, Anjora, Durg with more than 65 days postpartum anestrus were randomly divided into two groups. Animals (n = 7) of treatment group were given injection GnRH @ 10 µg intramuscularly on day 0, while those (n=7) of control group were given 2.5 ml normal saline intramuscularly. The animals in both the groups were monitored at three days interval for 24 days, i.e., on day 0, 3, 6, 9, 12, 15, 18, 21 and 24 using trans-rectal ultrasonography (5-7.5 MHz) for development of ovarian follicles, ovulation and corpus luteum formation. Significantly larger follicles were observed on day 3, 12 (p<0.05) and 24 (p<0.01) in GnRH treatment group than control group, suggesting folliculogenic and ovulatory effect of GnRH over 3- 12 days period, with establishment of cyclicity in anestrus cattle.